Connecting Science with Story Tale: How Sainsmatika Story Tale Book Decrease Science Anxiety of 4th Graders Student: Menghubungkan Sains dengan Dongeng: Bagaimana Buku Dongeng Sainsmatika Menurunkan Kecemasan Sains Siswa Kelas 4 - Putri, Agnestasia Ramadhani; Mustadi, Ali (SEJ (Science Education Journal), 2019)
This study investigating the effectiveness of using Sainsmatika story tale book towards student science anxiety. The study were an experimental research with pretest-posttest control-group design, involving 122 fourth-grade students in one of the district in Indonesia. Characteristically, this research employs quantitative data which were collected from the questionnaire results regarding science anxiety. The data were analyzed using statistical methods to calculate the values and determine the frequency as well as the mean of pretest and posttest scores in control and experimental classes. To determine the effectiveness of using fairytale books to reduce students’ science anxiety, the one-way analysis of ANOVA was used with a significant difference at the level of Sig < 0.05. The results of this study reveal that the use of sainsmatika-based fairytale books is effective to reduce science anxiety of the fourth-grade students with significancy 0.00 (<0.05).